A Spectroscopic Study on PtCl4(2−) Binding to Rabbit Skeletal Muscle G-Actin. Issue 3 (1995) - Zou Zou, Juan Juan; Sun Sun, Hong-Ye Hong-Ye; Wang Wang, Kui Kui
Abstract : It was found that the binding of PtCl 4 2 − to G-actin and the consequent conformational changes are different with those for hard acids. It is a two-step process depending on molar ratio PtCl 4 2 − /actin (R). In the first step, R less than 25, the PtCl 4 2 − ions are bound to sulfur-containing groups preferentially. These high-affinity sites determined by Scatchard approach are characterized by n 1 = 30 with average binding constant K 1 =1.0×10 7 M - 1 . The conformational changes are significant as characterized by N-(1-pyrenyl) maleimide(NPM) labeled fluorescence, intrinsic fluorescence and CD spectra. EPR spectroscopy of maleimide spin labeled(MSL) actin demonstrated that even PtCl 4 2 − binding is limited to a very small fraction of high-affinity sites(R<1), it can bring about a pronounced change of conformation. In the range of R=25-40, high-affinity sites accessible are saturated. In the second step(R>40), deep-buried binding sites turn out to be accessible as a result of the accumulated conformational changes. These new binding sites are estimated to be n 2 =26 with average binding constant K 2 =2.1×10 6 M -1 . Although in this step the quenching of intrinsic fluorescence goes on and the NPM-labled thiols moves to more hydrophilic environment, no change in α-helix content was found. These results suggested that with increasing in PtCl 4 2 − binding, the G-actin turns to an open and loose structure in a discontinuous mode.